Diabetes Distress and its Association with Depression in Patients with Type 2 Diabetes in Iran - Baradaran, Hamid R. (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Patients with diabetes experience some level of emotional distress varying from disease-specific distress to general symptoms of anxiety and depression. Since empirical data about symptom distress in relation to diabetes are sparse in Iran, this study was designed to assess the diabetes-specific distress in Iranian population. METHODS: Persian version of Diabetes Distress Scale (DDS) questionnaire was completed by volunteer outpatients on a consecutive basis between February 2009 and July 2010, in Endocrine Research Center (Firouzgar Hospital). Then, scheduled appointments were made with a psychiatrist in the same week following completion of the questionnaire. The psychiatrist was not aware about the results of this questionnaire and patients were interviewed based on DSM-IV criteria. RESULTS: One hundred and eighty-five patients completed the questionnaire and were interviewed by a psychiatrist. Fifty-two percent of the patients were females. The mean age was 56.06 (SD=9.5) years and the mean of duration of diabetes was 9.7 (SD=7.3) years. Sixty-five (35%) had distress. Among the patients with distress, 55% were females and 64% had lower grade of education. Eighty patients were diagnosed as having Major Depressive Disorder. There was a relation between Emotional Burden subscale and age (P=0.004), employment status (P=0.03), and also diabetes duration (P=0.02). The physician-related distress subscale was also related to the type of medication (P=0.009) and marital status (P=0.01). It has been shown that the regimen-related distress subscale was also related to age (P=0.003) and duration of diabetes (P=0.005). CONCLUSIONS: High prevalence rate of distress in the study highlights the significance of the need for identifying distress and also other mental health conditions in patients with diabetes in order to take collaborative care approaches.